Integrated Formal Methods 11th International Conference, IFM 2014, Bertinoro, Italy, September 9-11, 2014, Proceedings - Albert, Elvira; Sekerinski, Emil (Programming and Software Engineering, 2014)
This book constitutes the refereed proceedings of the 11th International Conference on Integrated Formal Methods, IFM 2014, held in Bertinoro, Italy, in September 2014. The 21 revised full papers presented together with 2 invited papers were carefully reviewed and selected from 43 submissions. The papers have been organized in the following topical sections: tool integration; model verification; program development; security analysis; analysis and transformation; and concurrency and control.